Komparasi Konsep Akad ¬al-Musammâ dan Gairu al-Musammâ dalam Fikih Muamalah dengan Kontrak Nominaat dan Innominaat dalam KUH Perdata - Aulia, Mulfi (STAINI Press, 2025)
In Article 1319 of the Civil Code, agreements are divided into named (nominaat) and unnamed (innominaat) agreements. Unnamed agreements arise and develop in society, while named agreements are regulated by law. Named contracts are recognized in the Civil Code, while innominaat contracts develop due to the principle of freedom of contract. The fiqh scholars divide contracts into al-musammâh contracts whose names are determined by shara' and gairu al-musammâh contracts determined by the community. The research conducted is qualitative in the form of a literature study with a juridical-normative approach. The results show that contracts and contracts in muamalah maliyah in Indonesia have similarities in terms of legal relations, legal subjects, achievements, and wealth. Although there are editorial differences between the pillars and essential elements, the legal consequences are the same: valid, void, or defective. Akad is divided into al-musammah and ghairu al-musammah, while contracts are nominaat and innominaat, based on the principle of freedom of contract. Not all contracts are subject to state regulation, because the human need to seek sustenance is very dynamic. The difference lies in the source of law and the application of substantial and procedural principles.